MA'AD 'ALY EDUCATION SYSTEM - M. Agus Kurniawan (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2022)
Ma'had Aly was formed in order to prepare cadres of scholars' who have scientific integrity, amaliah and khuluqiyah quality and have strategic value with justice-oriented,equality, openness, honesty, trust, and democracy. Ma'had Aly based on Ahlus Sunnah Wal Jama'ah with an Islamic basis means that Ma'had Aly is held, organized, and developed departing (point of depture) from Islamic teachings, the process of managing them in an Islamic way and towards what is idealized by Islamic education. The dynamics of Islamic boarding school education explained that the development of Islamic boarding schools has experienced a shift or change in several aspects along with the progress of the times and the development of science and technology. The discourse that develops in the dynamics of thought and practical experience of pesantren alumni seems to emphasize that pesantren are part of the community infrastructure which at a macro level has played a role in awakening the community to have ideals,